Prinsip Keadilan Dalam Teori Permintaan Dan Penawaran Ekonomi Islam - Putri, Falentia Wiliana; Latifah, Filda Fauzia; Ni’mah, Neha Faridatun; Gabriella, Susan Meylin; Hidayati, Amalia Nuril (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study discusses the influence of the principle of justice in demand and supply in the market for halal and ethical products within the context of Islamic economics. In the era of globalization and the development of digital technology, justice has become a crucial pillar in ensuring that economic transactions are not only financially beneficial but also align with moral and ethical values. This research employs a literature review method to analyze the relationship between the demand for halal products, market information transparency, and ethical supply. The analysis results indicate that the application of the principle of justice in economic transactions enhances consumer trust, which in turn stimulates demand. Furthermore, justice in market information and the avoidance of hoarding practices contribute to a fair and sustainable market equilibrium. This research emphasizes the importance of the government’s role in overseeing and intervening in the market to maintain justice and prevent exploitation. Thus, the application of the principle of justice can create a more stable and inclusive market.